Characterization of fragrant compounds in different types of high-salt liquid-state fermentation soy sauce from China. (1st November 2022) - Li, Jingyao; Zhang, Mengli; Feng, Xiaojuan; Ding, Tingting; Zhao, Yue; Sun, Chengguo; Zhou, Shengli; He, Jing; Wang, Chunling
Abstract: The aroma and sensory characteristics of 21 commercial high-salt liquid fermentation soy sauces (HLFSS) suitable for different edible methods were investigated by MS-based non-targeted metabolomics workflow using headspace solid-phase microextraction gas chromatography/mass spectrometry (HS-SPME-GC-MS) combined with sensory evaluation. A total of 325 compounds were detected, and 60 were considered aroma-active compounds. Light soy sauce (LSS) and premium soy sauce (PSS) for direct dipping contained more alcohols and esters. Aldehydes and furans were more abundant in dark soy sauce (DSS) used for stir-frying and braising. Principal component analysis (PCA) clustered LSS, DSS, and PSS into different quadrants and distinguished HLFSS of north-south origin. In addition, orthogonal partial least squares discriminant analysis (OPLS-DA) confirmed that the difference in volatile compounds of HLFSS in northern and southern China was related to local manufacturers' use of the Japanese and Cantonese fermentation processes. Sensory evaluations showed that LSS and PSS had prominent alcoholic and fruit aromas, while DSS had firmer caramel and malty aromas. Aroma-active compounds influenced regional differences in sensory attributes. The present study results will provide a theoretical basis for broadening industrial soy sauce production with different flavors. Highlights: A total of 325 volatile compounds were detected in soy sauce by HS-SPME-GC-MS. Alcohols and aldehydes were the main differences between soy sauces. The fermentation process caused regional differences between the north and south. The content of key aroma active compounds affected the sensory.